Straight to the top : becoming a world-class CIO - Smith, Gregory S., 1963- (Hoboken, N.J. : John Wiley & Sons, 2006)
You have what it takes to be a CIO. Do you have a strategy for getting there? Now you do."Gregory Smith has written the definitive work on how to achieve leadership success in IT. This well-written and carefully researched book is a must-read for any IT professional with aspirations toward the top IT spot
Straight to the Top: Becoming a World-Class CIO; Contents; Preface; Acknowledgements; Chapter 1: Key IT Skills to Have; Chapter 2: Methodologies, Projects, and IT Change Management; Chapter 3: IT Standards and Governance; Chapter 4: Learn the Business and Build Key Relationships; Chapter 5: Effective Communication Skills and Styles; Chapter 6: What Executive Recruiters Are Looking For; Chapter 7: Building the Right Network; Chapter 8: Vendor and Sports Management; Chapter 9: Contract Negotiation and Financial Management; Chapter 10: Risk/Reward and Knowing When to Jump.
Includes bibliographical references and index.
English.
John Wiley and Sons
Keywords: Chief information officers -- Vocational guidance; Information technology -- Management -- Vocational guidance; Information resources management -- Vocational guidance; Chefs des services de l'information -- Orientation professionnelle; Technologie de l'information -- Gestion -- Orientation professionnelle; Gestion de l'information -- Orientation professionnelle; BUSINESS & ECONOMICS -- Information Management; BUSINESS & ECONOMICS -- Knowledge Capital; Information resources management -- Vocational guidance